Moscow heat - Celentano, Jeff.; York, Michael, 1942-; Nevsky, Alexander; Tyson, Richard, 1961-; Madrid, Robert; Divoff, Andrew ([Universal City, CA] : Lightning Entertainment : Distributed by Visual Entertainment, 2005)
A retired diplomat and an NYPD dective seeking justice pursue a psychotic murderer to Moscow. When the detective is wounded and the diplomat is arrested, they are assigned to be deported by a Russian Police Captain.
Originally produced as a motion picture in 2004.
Special features: "Making of " documentary, photo gallery, Filmmakers' commentary.
Directed by Jeff Celentano ; music by Richard John Baker ; director of photography, John Aronson ; editor, Gib Jaffe, Ace.
Michael York, Alexander Nevsky, Richard Tyson, Robert Madrid , Andrew Divoff, Joanna Pacula, Adrian Paul.
DVD, region 1, anamorphic widescreen 1.78 :1 and fullscreen; Dolby Digital.
English dialogue, Spanish subtitles ; closed-captioned.